ANALISIS FITUR KALIMAT UNTUK PERINGKAS TEKS OTOMATIS PADA BAHASA INDONESIA - , Badrus Zaman, Drs. Edi Winarko, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
AutomaticÂ TextÂ SummarizationÂ (ATS)Â isÂ aÂ techniqueÂ toÂ createÂ aÂ summaryÂ ofÂ  theÂ  documentÂ  automaticallyÂ  byÂ  usingÂ  computerÂ  applicationsÂ  toÂ  produceÂ  theÂ mostÂ importantÂ informationÂ fromÂ theÂ originalÂ document.Â FeaturesÂ areÂ requiredÂ toÂ  performÂ  weightingÂ  ofÂ  sentences,Â  includingÂ  LogâTFISFÂ  (termÂ  frequencyÂ  indexÂ sentenceÂ  frequency),Â  sentenceÂ  location,Â  sentenceÂ  overlap,Â  titleÂ  overlapÂ  andÂ sentenceÂ  relativeÂ  length.Â  ThisÂ  researchÂ  conductedÂ  anÂ  analysisÂ  ofÂ  fiveÂ  featureÂ extractionsÂ inÂ orderÂ toÂ determineÂ theÂ weightsÂ ofÂ eachÂ featureÂ thatÂ willÂ getÂ theÂ resultsÂ ofÂ aÂ coherentÂ summary.Â TheÂ fiveÂ featuresÂ areÂ implementedÂ inÂ automatedÂ textÂ summarizationÂ systemÂ inÂ IndonesianÂ languageÂ thatÂ wasÂ developedÂ usingÂ theÂ methodÂ ofÂ relativeÂ importanceÂ ofÂ topics.Â ResultsÂ  fromÂ  experimentsÂ  showÂ  thatÂ  sentenceÂ  locationÂ  featureÂ  hasÂ  theÂ highestÂ  FâMeasuresÂ  namelyÂ  0.46Â  andÂ  thenÂ  consecutiveÂ  sentenceÂ  overlap,Â  titleÂ overlap,Â sentenceÂ relativeÂ lengthÂ andÂ LogâTFISF,Â withÂ aÂ valueÂ ofÂ 0.42,Â 0.42,Â 0.35Â andÂ 0.32.Â RelativeÂ weightsÂ ofÂ featureÂ consecutiveÂ fromÂ theÂ largestÂ areÂ sentenceÂ location,Â sentenceÂ overlap,Â titleÂ overlap,Â sentenceÂ relativeÂ lengthÂ andÂ LogâTFISFÂ withÂ  aÂ  valueÂ  ofÂ  0.25,Â  0.22,Â  0.22,Â  0.19Â  andÂ  0.12.Â  TheseÂ  relativeÂ  weightsÂ  areÂ implementedÂ onÂ ATS,Â soÂ weÂ getÂ accuracyÂ ofÂ 70.62%.Â ItÂ isÂ moreÂ accurateÂ 2,86%Â thanÂ withoutÂ relativeÂ weightsÂ whichÂ accuracyÂ ofÂ 67,72%.Â